ijee 2022
DOI: 10.48165/ijee.2022.58232
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Farmers towards Custom Hiring Service Centres in Tumakuru District of Karnataka

Abstract: The study was carried out in Tumakuru district of Karnataka state during the year 2019- 20. Eight taluks and 130 farmers were selected where the Custom Hiring Service Centres were working effectively. The majority of the farmers strongly agreed with helps in overcoming the problem of labour through custom hiring service centre, for visiting farmers field after completion of the work, farmers pays only for the number of acres or number of hours used. The overall perception of farmers indicated that 43.8 % were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…It is observed that maximum numbers of respondents (75.00%) were having moderate perception regarding CHS followed by good perception (13.25%), whereas 11.25 per cent respondents had poor perception about CHS. The finding is supported with the work of Anonymous (2012); Singh et al, (2014); Gudadur & Jahanara (2017); Shobha et al, (2018) & Kadaraiah et al, (2022). The reason for this might be due to the fact that the farm mechanization is slowly increasing in the region of the study area and farmers still had not much understanding of the improved agricultural implements used in the cultivation of various crops.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…It is observed that maximum numbers of respondents (75.00%) were having moderate perception regarding CHS followed by good perception (13.25%), whereas 11.25 per cent respondents had poor perception about CHS. The finding is supported with the work of Anonymous (2012); Singh et al, (2014); Gudadur & Jahanara (2017); Shobha et al, (2018) & Kadaraiah et al, (2022). The reason for this might be due to the fact that the farm mechanization is slowly increasing in the region of the study area and farmers still had not much understanding of the improved agricultural implements used in the cultivation of various crops.…”
Section: Resultssupporting
confidence: 80%
“…Agriculture is majorly dependent on the availability of land, labour and capital in which agriculture labour may be considered as one of the most important input in farm operations. One of the biggest issues that Indian farmers in rural areas experience is a lack of agricultural labour (Kadaraiah et al, 2022). The rise in the labour cost has created new challenges for the farmers in gaining decent returns from their produce.…”
Section: Introductionmentioning
confidence: 99%
“…KVKs and extension wings of universities need to play a very key role in sensitizing the farmers on custom hiring adoption. The findings highlight the crucial role of stakeholder participation in both the delivery and adoption of services provided by extension agencies (Kadaraiah & Jirli, 2022) [7] . There is a need to innovate Custom Hiring model by institutionalization for high cost farm machinery such as combine harvesters, sugarcane harvester, Onion transplanter, laser guided land leveler etc.…”
Section: Discussionmentioning
confidence: 86%
“…A study on the perception of farmers towards Custom Hiring Service Centres (CHSC) in Tumakuru District of Karnataka revealed the overall perception of farmers indicating that 43.8% were categorized under favourable level of perception towards CHSC. The small and medium-sized farmers could not possess the modern machinery, due to high hiring charges with private vendors they were unable to take the farm machinery for rent and some of the large farmers also were in great need of the modern machinery thus they require modern machinery through custom hiring [71].…”
Section: Perception Of Farmers Regarding the Services Rendered By Cus...mentioning
confidence: 99%